Potensi Overkriminalisasi Dalam Tindak Pidana Agama: Analisis Kritis Terhadap Perumusan Kitab Undang-Undang Hukum Pidana Nasional Baru (UU No. 1 Tahun 2023) - Fernando, Zico Junius; Wulandari, Sri; Putra, Panca Sarjana (Badan Strategi Kebijakan Hukum dan HAM, 2023)
Overcriminalization in the context of criminal law refers to the phenomenon where too many behaviors are defined as criminal offenses, which ultimately results in the expansion of law enforcement powers and an increase in the number of individuals caught up in the criminal justice system. This study examines overcriminalization in the formulation of religious offenses contained in Law Number 1, the Year 2023 on the Criminal Code (KUHP), focusing on Article 302 on incitement of a person to no religion or belief adopted in Indonesia and its impact on atheists or non-religious communities. The analysis highlights several important issues, such as the unclear definition of